The Allocation of Attention to Learning of Goal-Directed Actions: A Cognitive Neuroscience Framework Focusing on the Basal Ganglia - Franz, Liz (Frontiers in Psychology, 2012)
The present paper builds on the idea that attention is largely in service of our actions. A framework and model which captures the allocation of attention for learning of goal-directed actions is proposed and developed. This framework highlights an evolutionary model based on the notion that rudimentary brain functions have become embedded into increasingly higher levels of networks which all contribute to adaptive learning. Background literature is presented alongside key evidence based on experimental studies in the so-called ‘split-brain’ (surgically divided cerebral hemispheres) with a key focus on bimanual actions. The proposed multilevel cognitive-neural system of attention is built upon key processes of a highly-adaptive basal-ganglia-thalamic-cortical system. Although overlap with other existing findings and models is acknowledged where appropriate, the proposed framework is an original synthesis of cognitive experimental findings with supporting evidence of a neural system and a carefully formulated model of attention. It is the hope that this new synthesis will be informative in fields of cognition and other fields of brain sciences and will lead to new avenues for experimentation across domains.